Crisis in LAC : Infrastructure Investment, Employment and the Expectations of Stimulus - Schwartz, Jordan; Andres, Luis; Dragoiu, Georgeta (World Bank, Washington, DC, 2014)
Infrastructure investment is a central part of the stimulus plans of the Latin America and the Caribbean (LAC) region as it confronts the growing financial crisis. This paper estimates the potential effects on direct, indirect, and induced employment for different types of infrastructure projects with LAC-specific variables. The analysis finds that the direct and indirect short-term employment generation potential of infrastructure capital investment projects may be considerable averaging around 40,000 annual jobs per United States (U.S.) 1 billion dollars in LAC, depending upon such variables as the mix of subsectors in the investment program; the technologies deployed; local wages for skilled and unskilled labor; and the degrees of leakages to imported inputs. While these numbers do not account for substitution effect, they are built around an assumed basket of investments that crosses infrastructure sectors most of which are not employment-maximizing. Albeit limited in scope, rural road maintenance projects may employ 200,000 to 500,000 annualized direct jobs for every U.S. 1 billion dollars spent. The paper also describes the potential risks to effective infrastructure investment in an environment of crisis including sorting and planning contradictions, delayed implementation and impact, affordability, and corruption.